Botanical and microbial insecticides application in aquaponics - is there a risk for biofilter bacteria and fish? - Rašković, Božidar; Gebauer, Radek; Folorunso, Ewumi Azeez; Božić, Gavrilo; Velíšek, Josef; Dvořák, Petr; Bořík, Adam; Grabic, Roman; Mráz, Jan (Frontiers in Marine Science, 2022)
Aquaponics is a food production system that combines aquaculture with hydroponics. The simultaneous existence of fish, beneficial bacteria and plants in the same water loop predisposes the fish and bacteria to a possible detrimental effect of plant protection products. Additionally, there is an inadequate exploration of scientific studies on the impact of pesticides on fish and bacteria in aquaponics systems. This study investigated the effects of three commercial insecticides based on the following active ingredients: pyrethrum, azadirachtin, and spinosad, on aquaponics systems. Due to ethical concerns in animal testing, applying insecticides directly to aquaponics setup was impossible. Therefore, three separate experiments were conducted: (1) Pesticide runoff rate – in which insecticides were applied to basil (Ocimum basilicum) plants grown in two hydroponic systems: media bed and floating raft. The concentrations of applied insecticides were measured in the water of nutrient solutions of the hydroponics after 1, 3, 6, 12, 24, 36, 48, 72 and 96h to establish a pattern of degradation of insecticides. The result from this experiment showed that pyrethrum and spinosad were detected in unquantifiable concentrations in the nutrient solutions. Hence, further experiments were conducted only with azadirachtin. In a biofilter trial (2) – azadirachtin, at three concentrations (1.5 µg L-1; 7.5 µg L-1; and 15 µg L-1), was added to a running biofilter to investigate the effects on nitrifying bacteria. Mild effects were recorded in the nitrification and bacteria microbiome. In the third trial (3) – Nile tilapia (Oreochromis niloticus) were exposed to similar concentrations of azadirachtin for seven days (and the same period for recovery) to investigate effects on fish hematology, blood biochemistry, antioxidative enzymes in the brain, gills, muscle, liver and intestine and histopathology of gills and liver. Results showed mild effects in hematology and biochemistry profile in fish and higher levels of lipid peroxidation in the liver during the exposure. The results indicate a safe use of pyrethrum and spinosad in aquaponics setup, while azadirachtin has to be used with care, especially in coupled aquaponics systems.